Ethnic differences in case fatality following an acute ischaemic heart disease event in New Zealand: ANZACS-QI 13. (November 2016) - Grey, Corina; Jackson, Rod; Wells, Susan; Marshall, Roger; Mehta, Suneela; Kerr, Andrew J
Background: The aim of this study was to investigate ischaemic heart disease (IHD) case fatality in high-risk ethnic populations in New Zealand. Design: This is a national data-linkage study using anonymised hospitalisation and mortality data. Methods: Linked individual patient data were used to identify 35–84-year-olds who experienced IHD events (acute IHD hospitalisations and/or deaths) in 2009–2010. Subjects were classified as: (i) hospitalised with IHD and alive at 28 days post-event; (ii) hospitalised with IHD and died within 28 days; (iii) hospitalised with a non-IHD diagnosis and died from IHD within 28 days; or (iv) died from IHD but not hospitalised. Multinomial logistic regression was used to estimate the proportion of people in each group, as well as overall 28-day case fatality, adjusted for ethnic differences in demographic and comorbidity profiles. Results: A total of 26, 885 people experienced IHD events (11.3% Māori, 4.0% Pacific and 2.5% Indian); 3.3% of people died within 28 days of IHD hospitalisations, 5.1% died of IHD within 28 days of non-IHD hospitalisations and 13.0% died of IHD without any recent hospitalisation. Overall adjusted case fatality was 12.6% in Indian, 20.5% in European, 26.0% in Pacific and 27.6% in Māori people. Compared to Europeans, the adjusted odds of death were approximately 50% higher in Māori and Pacific people and 50% lower in Indians, regardless of whether they were hospitalised. Conclusions: Major ethnic inequalities in IHD case fatality occur with and without associated hospitalisations. Improvements in both primary prevention and hospital care will be required to reduce inequalities.